Echocardiographic and biochemical profile in children with celiac disease - Y M, Bhavika; Dewan, Vivek; Nath, Ranjit K; Yadav, T P; Mittal, Hema; Yadav, Ajeet Kumar; Nabum, Surat (Indian Journal of Child Health, 2020)
Background: A number of heart diseases such as autoimmune myocarditis, cardiomyopathy, and ischemic heart disease are recently being reported among celiac patients. Studies have also demonstrated subclinical cardiac dysfunction and clustering of many traditional cardiovascular risk factors in children with celiac disease. Objective: The present study was conducted for echocardiographic and biochemical assessment of children with celiac disease. Materials and Methods: A cross-sectional observational study was conducted among 36 children (aged 1–16 years) who were newly diagnosed with celiac disease and age- and sex-matched controls. Venous blood samples were assessed for serum C-reactive protein (CRP), folic acid, Vitamin B12, and homocysteine levels, and fasting lipid profile including total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C) and low-density lipoprotein cholesterol (LDL-C), and triglycerides (TG) levels using appropriate methods. Echocardiographic parameters were measured by M-mode ultrasonography measuring left atrial dimension (LAD), left ventricular end-diastolic dimension (LVEDD), right ventricular diastolic diameter (RVDD), interventricular septal thickness at end-diastole (IVSd), left ventricular posterior wall thickness at end-diastole (LVPWd), aortic root dimension (ARD), and ejection fraction (EF). Results: Among the echocardiographic parameters, EF was significantly lower while other parameters such as LAD, LVEDD, RVDD, IVSd, LVPWd, and ARD showed no significant increase among the cases. Significantly lower levels of TC, HDL-C, and LDL-C with normal TG, CRP, Vitamin B12, and folic acid levels with significantly increased serum homocysteine levels were noted among cases. Conclusion: A significant difference in EF and the presence of biochemical risk factors for cardiovascular diseases warrants further detailed evaluation and follow-up with regular monitoring of cardiac functions.